Eksplorasi Pembelajaran IPAS di Sekolah Dasar: Systematic Literatur Review - Sari, Diah Novita; Asiah, Nur; Afriyadi, Muhammad Muchsin (Universitas Nusantara PGRI Kediri, 2026)
This study aims to map trends in Natural and Social Sciences (IPAS) learning in elementary schools for the 2021-2025 period, analyze technology integration, and identify future research opportunities. The method used was a Systematic Literature Review (SLR) of 33 scientific articles using the PRISMA protocol. The results showed that the learning model trend was dominated by a constructivist approach, with the Inquiry model being the most dominant (11 articles), followed by Problem-Based Learning (7 articles) and Discovery Learning (6 articles). Learning strategies shifted towards Digital-Based Learning and gamification through group discussions, environmental observation, and innovative methods such as Window Shopping. Technology integration through digital media such as Augmented Reality (AR), Canva, and gamification platforms (Kahoot, Quizizz, Wordwall) was proven effective in increasing learning motivation by up to 93.23%, strengthening student engagement, and visualizing abstract concepts concretely. Despite the positive impact, the main challenge lies in the stability of internet infrastructure. Future research opportunities include exploring cooperative models such as Student Facilitator and Explainer (SFAE) and developing higher-order thinking skills (HOTS) variables. In conclusion, the synergy between active learning models and interactive digital media is key to effective science learning in elementary schools.